2022
DOI: 10.19206/ce-142167
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the market structure of long-distance transport vehicles in the context of retrofitting diesel engines with modern dual-fuel systems.

Abstract: The demands placed on vehicles are constantly increasing. European legislation has forced commercial vehicle manufacturers to develop ever more powerful and dynamic engines with low fuel consumption. With the appearance of exhaust gas standards, truck manufacturers realized that it was necessary to improve the fuel supply system so that the combustion process was more efficient. To achieve this the fuel injected into the cylinders had to be finer in order to mix more easily with air. High-pressure unit injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…Work has shown that hydrogen is a potentially futureproof option because it reduces specific fuel consumption [3,4,6,7], increases engine performance, improves efficiency and thermal efficiency [8][9][10]. It has also been found that, by increasing the dosage of diesel, more hydrogen can be supplied without adversely affecting the working process [11,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Work has shown that hydrogen is a potentially futureproof option because it reduces specific fuel consumption [3,4,6,7], increases engine performance, improves efficiency and thermal efficiency [8][9][10]. It has also been found that, by increasing the dosage of diesel, more hydrogen can be supplied without adversely affecting the working process [11,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%